OVERVIEW OF CURRENTLY USED WIRELESS ELECTRICAL VEHICLE CHARGING SOLUTIONS - Dobrzański, Damian (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2018)
This article describes the current systems for wireless electrical vehicles charging available for use and ideas how to improve efficiency of them, differences between active and passive (static) contactless charging and also institutions and companies which work on development this kind of technology.